Structures of the direct addressing in texts of the printed advertisement (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article the features of the use of facilities of the direct addressing are examined in texts of the printed advertisement.  The structural types of incentive sentences are educed and the most frequency functionally-semantic groups of verbs that provide realization of the communicative-pragmatic guidance of addressing are certain.
Keywords: the printed advertisement; direct addressing; incentive suggestion; semantic groups of verbs